An Efficient Route Selection based on AODV Algorithm for VANET - Kadhim, Nassir; Mohammed, Muamer N.; Mazlina, Abdul Majid; Mohamd, Sinan Q.; Tao, Hai (Informatics Publishing Limited, 2016)
Road safety is an all-time global concern. Every day a large number of human lives are lost with many sustaining a disability as a result of their injury due to car accidents and delay in calling the rescue services. Recently, Intelligent Transportation Systems (ITS) have emerged as an efficient way of improving interpretation of transportation systems and enhancing travel safety. Accident detection systems are one of the most effective (ITS) tools. The accident detection system which based on Global Positioning System (GPS) and Global System for Mobile communication (GSM) can be accomplished though one or several sensors, the system can gather the information and coordinates of accident spot, then send this data to the rescue services center over a network link in the shortest time, In this paper, we propose an enhanced system that composed of a GPS receiver, Vibration sensor, GSM Modem and integrated with Vehicular AD-Hoc Network (VANET). The employment of (VANET) assists to increase the data delivery by providing a second path to send an emergency message to The Rescue Services Center (RSC) whenever an accident located at out of coverage area of GSM network. Simulation tested two of distance ranges among nodes (Long & Short) and the result shown that VANET modified algorithm based on average signal strength has the advantage of choosing the optimum route to deliver data and own enhanced ratio according to the distances (17.5% & 24.1%) by comparing with a maximum signal strength route.